Studies on the Indian species of the genus Anagyrus Howard, 1896 (Hymenoptera: Encyrtidae). - Subba Rao, B. R.; Rai, P. S. (Contributions to Entomology = Beiträge zur Entomologie, 1970)
The genus Anagyrus was established by Howard in 1896. So far only a couple of species were known from India. Therefore a systematic collection of scale pests ... Nomenclatural Acts comperei Subba Rao & Rai, 1970 (Anagyrus), spec. n. dehliensis Subba Rao & Rai, 1970 (Anagyrus), spec. n. nigroradiclatus Subba Rao & Rai, 1970 (Anagyrus), spec . n.